In Vitro Cytokine Expression and In Vivo Healing and Inflammatory Response to a Collagen-Coated Synthetic Bone Filler. (18th April 2016) - Bollati, Daniele; Morra, Marco; Cassinelli, Clara; Lupi, Saturnino Marco; Rodriguez y Baena, Ruggero
Abstract : The goal of the present work was to investigate the relationship between in vivo healing and inflammatory response and in vitro cytokine expression by macrophages of a synthetic bone filler (25% hydroxylapatite-75% β -tricalcium phosphate) bearing a surface nanolayer of collagen. A clinically accepted, state-of-the-art xenograft material was used as a "negative control, " that is, as a material that provides the correct clinical response for the intended use. In vitro data show that both materials exert a very low stimulation of proinflammatory cytokines by macrophages, and this was confirmed by the very mild inflammatory response detected in in vivo tests of local response in a rabbit model. Also, in vitro findings suggest a different mechanism of healing for the test and the control material, with a higher regenerative activity for the synthetic, resorbable filler, as confirmed by in vivo observation and literature reports. Thus, the simple in vitro model adopted provides a reasonable forecast of in vivo results, suggesting that new product development can be guided by in vitro tuning of cell-materials interactions.